Formation of Emotional Culture of the Future Teacher of Choreography in the Process of Choreographic Activity - Olena Yefymchuk (Pedagogical Discourse, 2013)
The process of forming of socially important characteristics of a personality is analyzed in the article. It is impossible without an emotional component. In this case it is very important to have the skill of regulation of your own emotions. This skill is the basis of the emotional culture of future teacher of choreography. This article determines  the peculiarities of the process of teaching emotional culture of the future teacher of choreography. The emotional culture is one of the components of pedagogical work which is comprised of a system of knowledge and skills. They are aimed to the adequacy of the emotional response.